2022
DOI: 10.1371/journal.pone.0269649
|View full text |Cite
|
Sign up to set email alerts
|

A natural history study to track brain and spinal cord changes in individuals with Friedreich’s ataxia: TRACK-FA study protocol

Abstract: Introduction Drug development for neurodegenerative diseases such as Friedreich’s ataxia (FRDA) is limited by a lack of validated, sensitive biomarkers of pharmacodynamic response in affected tissue and disease progression. Studies employing neuroimaging measures to track FRDA have thus far been limited by their small sample sizes and limited follow up. TRACK-FA, a longitudinal, multi-site, and multi-modal neuroimaging natural history study, aims to address these shortcomings by enabling better understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Furthermore, dMRI metrics have been shown to detect the progression of microstructural changes with high sensitivity [21]. Finally, two large international consortia, READISCA [5] for SCA1 and SCA3 and TRACK-FA [6] for FRDA, are currently using the proposed AGI dMRI protocol for clinical trial readiness studies.…”
Section: Diffusion Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, dMRI metrics have been shown to detect the progression of microstructural changes with high sensitivity [21]. Finally, two large international consortia, READISCA [5] for SCA1 and SCA3 and TRACK-FA [6] for FRDA, are currently using the proposed AGI dMRI protocol for clinical trial readiness studies.…”
Section: Diffusion Mrimentioning
confidence: 99%
“…Prospective longitudinal studies will be particularly important to validate MRI biomarkers for clinical trial readiness. While several multi-site longitudinal imaging studies are ongoing in common degenerative ataxias [5,6], the majority of the MRI studies thus far have demonstrated cross-sectional group differences, and more longitudinal studies are needed to evaluate the sensitivity of MR biomarkers to progressive pathology [3].…”
Section: Introductionmentioning
confidence: 99%
“…Images of FRDA and MS patients were selected to account for anatomical variability in DN caused by neurodegeneration throughout the course of the diseases. The corresponding MRI acquisition protocols have been previously published 11,23,24 and are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The ethics committee or institutional review board (IRB) respective to each project data source or site approved the use or ethics waiver for this retrospective study, and all participants provided written informed consent prior to original data collection. The TRACK-FA steering committee approved the data use, and IRB reference numbers were previously published 23 (Monash Health Human Research Ethics Committee: RES-20-0000-139A; Children’s Hospital of Philadelphia: IRB 20-017611; University of Minnesota: IRB STUDY00009047; University of Florida: IRB202000399; RWTH Aachen University: EK195/20; University of Campinas (CAAE NO): 83241318.3.1001.5404; McGill IRB Approved Project Number: 2022-8676). Ethics approval was obtained independently for the remaining studies, respectively: Ethical Committee “Carlo Romano” of the University of Naples “Federico II” (Naples A: 209/13, Naples B: 47/15), Monash University Human Research Ethics Committee (IMAGE-FRDA: 13201B, INFLAM-FRDA: 7810), and University of Minnesota IRB (1210M22281).…”
Section: Methodsmentioning
confidence: 99%
“…The spine-generic protocol has been adopted in recent multi-center studies involving patients with multiple sclerosis, 25 , 26 traumatic spinal cord injury, 27 degenerative cervical myelopathy, 28 and Friedreich’s ataxia. 29 …”
Section: Standardized Acquisition Protocolmentioning
confidence: 99%